HUBUNGAN ANTARA KEPUASAN KERJA DAN KOMITMEN ORGANISASI PADA PEKERJA LEPAS BIRO KONSULTAN - Ginanjar Ginanjar; Benedicta P. Dwi Riyanti (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2015)
With job satisfaction, a company can better maintain the commitment of its employees. This study aims to explore the applicability of the assumption for freelance workers. For example, freelance workers in Bureau Consultant PT. B experience close working relationship, have co-workers from the same college, opportunity to use their expertise, and interesting tasks which become sources for their job satisfaction. Satisfying with their job can make them able to commit to Bureau Consultant PT. B despite having a job at another company. The participant of this study are all freelancer working at the Bureau Consultant PT. B. The quantitative approach used in this study with two questionnaires, Minessota Satisfaction Questionnaire and Organizational Commitment Questionnaire. Results of the study show that there is a positive relationship between job satisfaction with affective commitment and normative commitment, while job satisfaction doesn’t have a relationship with continuance commitment. Therefore, the more freelancer in Bureau Consultant PT. B satisfied with their work, they will be more committed emotionally to Bureau Consultant PT. B and morally feel obliged to remain in Bureau Consultant PT. B. Based on the results, it is suggested to Bureau Consultant PT. B to pay attention to three aspects of job satisfaction are still lacking, the aspect of social status, aspects of the opportunity to move forward, the aspect of certainty and security, to facilitate and give confidence to the freelancers to hold the higher responsibility so that they can better demonstrate their competencies at work. This will lead to more satisfied workers. This study indicate that it is possible to build organizational commitment for freelance worker by managing their job satisfaction.